Perovskite-type composite oxide powder

By using perovskite-type composite oxide powder containing specific elements and controlling its particle size distribution and specific surface area, the problem of insufficient conductivity of SOFC air electrodes is solved, and higher conductivity and fuel cell performance are achieved.

CN119403766AInactive Publication Date: 2025-02-07DOWA ELECTRONICS MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202480002940.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-30
Filing Date
2024-03-12
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing SOFC air electrode materials have insufficient electrical conductivity and are difficult to meet the needs of higher performance.

Method used

Perovskite-type composite oxide powders containing La and selected from Sr, Ca, Co, Ni, Mn, Fe are used, and a certain ratio range is satisfied through specific particle size distribution and specific surface area control to improve conductivity.

Benefits of technology

Higher conductivity is achieved, the performance of SOFC air poles is improved, thereby improving the efficiency of the overall fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179041230000151
    Figure BDA0005179041230000151
  • Figure HDA0005179041240000011
    Figure HDA0005179041240000011
Patent Text Reader

Abstract

This perovskite-type composite oxide powder contains La and further contains at least one element selected from the group consisting of Sr, Ca, Co, Ni, Mn, and Fe, has a BET specific surface area of less than 6.0 m2 / g, and satisfies formula (1). 1 < = {(D90B-D10B) / D50B} / {(D90A-D10A) / D50A} < = 2.1 (1) In the formula, D10, D50, and D90 are volume-based cumulative 10% particle diameter, cumulative 50% particle diameter, and cumulative 90% particle diameter when measured using a particle size distribution measurement device using a laser diffraction / scattering method, subscript "A" is the particle diameter after ultrasonic dispersion, and subscript "B" is the particle diameter before ultrasonic dispersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to composite oxide powders having a perovskite-type structure, and more specifically, to composite oxide powders preferred for use as air electrode materials in solid oxide fuel cells (SOFCs). Background Technology

[0002] Among various types of fuel cells, SOFCs (Solar-Oriented Fuel Cells) offer high power generation efficiency and can utilize a wide variety of fuels, thus they are being developed as a next-generation power generation device with low environmental impact. A single SOFC cell has a structure consisting of a porous air electrode (cathode), a dense solid electrolyte containing oxide ion conductors, and a porous fuel electrode (anode) stacked sequentially (see [link to documentation]). Figure 1 In SOFC operation, gases containing O2 (oxygen) such as air are supplied to the air electrode, while fuel gases such as H2 (hydrogen) are supplied to the fuel electrode. Under these conditions, when an electric current is applied to the SOFC, O2 is reduced to O2 at the air electrode. 2- Anion (oxygen ion). Furthermore, this O... 2- Anions pass through the solid electrolyte to the fuel electrode, where they oxidize H2 and release electrons. This generates electrical energy (i.e., electricity generation).

[0003] The operating temperature of SOFCs used to be around 800℃ to 1000℃, but in recent years, there has been a focus on lowering the operating temperature of SOFCs. Even so, the minimum temperature of SOFCs in actual use is still high, reaching over 600℃.

[0004] Due to this battery structure and high operating temperature, the materials for the air electrode of SOFC are basically required to have the following characteristics: high oxygen ion conductivity, high electronic conductivity, thermal expansion comparable to or similar to that of the electrolyte, high chemical stability, good compatibility with other constituent materials, porous sintered body, and certain strength.

[0005] As the material for the air electrode of this type of solid oxide fuel cell, the applicant proposed in Patent Document 1 a material of general formula ABO. 3-δ The perovskite-type composite oxide powder shown is a microcrystal diameter of 20 nm or more and 100 nm or less, determined by the Williamson-Hall method. In the formula, δ represents the oxygen vacancy amount, 0 ≤ δ < 1, the element contained in site A is La, and the elements contained in site B are Co and Ni (Patent Document 1).

[0006] Furthermore, in Patent Document 2, La was proposed as the material for the electrode layer or lead layer of the electrode used as a gas sensor element. a M b Nic O x The conductive oxide shown has a perovskite-type oxide crystal structure, where M is one or more of Co and Fe, and a+b+c=1, 1.25≤x≤1.75.

[0007] In addition, Patent Document 3 proposes an air electrode raw material powder, which is a perovskite composite oxide powder represented by the general formula ABO3, wherein A contains one or more elements selected from the group consisting of La and rare earth elements and one or more elements selected from the group consisting of Sr, Ca and Ba, and B contains one or more elements selected from the group consisting of Mn, Co, Fe, Ni and Cu. Furthermore, the average particle size of the air electrode raw material powder is less than 1 μm and the width of the particle size distribution is limited to a specified range.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: International Publication No. 2022 / 013903

[0011] Patent Document 2: Japanese Patent Application Publication No. 2018-112490

[0012] Patent Document 3: Japanese Patent Application Publication No. 2006-32132 Summary of the Invention

[0013] Problems to be solved by the invention

[0014] The material used for the air electrode of SOFC should ideally have the lowest possible resistance and highest conductivity. In recent years, there has been a desire to further improve its performance.

[0015] Therefore, the object of the present invention is to obtain higher conductivity in perovskite-type composite oxide powders with a specific composition.

[0016] Solutions for solving problems

[0017] The perovskite-type composite oxide powder according to embodiments of the present invention for achieving the aforementioned objective is characterized by containing La and further containing at least one element selected from the group consisting of Sr, Ca, Co, Ni, Mn, and Fe, wherein the BET specific surface area of ​​the perovskite-type composite oxide powder is less than 6.0 m². 2 / g, and satisfies the following equation (1).

[0018] 1≤{(D 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D50A}≤2.1···(1)

[0019] In the formula,

[0020] D 10A D 50A D 90A The cumulative 10% particle size (D) on a volume basis is used when measuring the particle size distribution of a slurry containing perovskite-type composite oxide powder using a particle size distribution measuring device employing laser diffraction / scattering. 10A ), cumulative 50% particle size (D 50A ), cumulative 90% particle size (D 90A The slurry containing perovskite-type composite oxide powder was obtained by adding 0.15 g of perovskite-type composite oxide powder to 60 mL of 500 ppm sodium hexametaphosphate aqueous solution (dissolved in deionized water) and dispersing it for 30 seconds using an ultrasonic homogenizer at an ultrasonic power of 300 μA.

[0021] D 10B D 50B D 90B This refers to the cumulative 10% particle size (D) on a volume basis when measuring slurries containing perovskite-type composite oxide powder using a Microtrac particle size distribution measuring device. 10B ), cumulative 50% particle size (D 50B ), cumulative 90% particle size (D 90B The slurry containing perovskite-type composite oxide powder is obtained by adding 0.15 g of perovskite-type composite oxide powder to 60 mL of 500 ppm sodium hexametaphosphate aqueous solution (dissolved in deionized water).

[0022] In the perovskite-type composite oxide powder of the described embodiment, the cumulative 50% particle size (D) of the slurry without ultrasonic homogenization is considered on a volume basis. 50B The preferred size is between 0.5 μm and 1.3 μm.

[0023] In addition, according to the present invention, an air electrode for a solid oxide fuel cell is provided, which is formed comprising the perovskite-type composite oxide powder described in any one of the above claims.

[0024] In addition, according to the present invention, a solid oxide fuel cell is provided, which includes a fuel electrode, a solid electrolyte and an air electrode, wherein the solid oxide fuel cell uses the air electrode described above as the air electrode.

[0025] It should be noted that, in this specification, the BET specific surface area is determined by the measurement method described in the examples below.

[0026] The effects of the invention

[0027] According to the present invention, perovskite-type composite oxide powders with higher conductivity can be realized. By using such perovskite-type composite oxide powders, air electrodes and fuel cells with high conductivity can be realized. Attached Figure Description

[0028] Figure 1 This is a cross-sectional structural diagram showing an example of a solid oxide fuel cell. Detailed Implementation

[0029] The perovskite-type composite oxide powder (hereinafter sometimes simply referred to as "composite oxide powder") of the present invention contains La (lanthanum) and also contains at least one element selected from the group consisting of Sr (strontium), Ca (calcium), Co (cobalt), Ni (nickel), Mn (manganese), and Fe (iron).

[0030] When other formulations are used, the composite oxide powder involved in this invention is made of the general formula ABO. 3-x This indicates that site A contains La and optionally includes at least one of Sr and Ca, and site B contains at least one element selected from the group consisting of Co, Ni, Mn, and Fe. x represents the amount of oxygen vacancy, including 0, and the value of x ranges from 0 to x < 1.

[0031] Among these components, the general formula ABO 3-x In this representation, it is preferred that site A contains La and Sr, and site B contains Mn. The amounts of Sr at site A and Mn at site B can be adjusted arbitrarily. As a general formula, it can be represented as LaSr y Mn 1-y O 3-x In the formula, y is preferably 0.1≤y≤0.9, and more preferably 0.3≤y≤0.85. The range of x is 0≤x<1.

[0032] In addition, according to other formulations, the composite oxide powder involved in this invention is made of the general formula ABO 3-x This indicates that site A contains La. 1-(a+b) Sr a Ca b Site B contains at least one element selected from the group consisting of Co, Ni, Mn, and Fe. x represents the amount of oxygen vacancy, including 0, and the value of x ranges from 0 to x < 1. Additionally, the ranges of a and b are 0 < a < 1 and 0 ≤ b < 1, respectively.

[0033] The composite oxide powder involved in this invention only needs to have a perovskite structure as its main component, and may contain other unavoidable impurity phases caused by raw materials, etc. A single-phase perovskite structure is preferred.

[0034] One of the main features of the composite oxide powder involved in this invention is that its BET specific surface area, measured by the BET single-point method, is less than 6.0 m². 2 / g. When the BET specific surface area of ​​the composite oxide powder is less than 6.0m². 2 At a concentration of / g, when the composite oxide powder is slurried or coated to form an air electrode material, the increase in viscosity is suppressed, the coatability of the slurry or coating is improved, and this contributes to conductivity. A more preferred BET specific surface area for the composite oxide powder is 4.5m². 2 / g or less.

[0035] On the other hand, the BET specific surface area of ​​the composite oxide powder is preferably 0.1 m². 2 / g or more, further preferably 2.0m 2 / g or more. When the BET specific surface area of ​​the composite oxide powder is 0.1m². 2 When the concentration of composite oxide powder is above a certain level, a suitable number of fine pores can be formed on the surface of the air electrode when the composite oxide powder is used to form the air electrode of the fuel cell. This increases the contact area with the gas and improves the exchange efficiency when the fuel cell is constructed.

[0036] Another key feature of the composite oxide powder involved in this invention is that it satisfies the stated formula (1). The inventors have conducted various studies with the aim of improving the conductivity of the air electrode in fuel cells, and have obtained the following new insight: when the proportion of aggregated powder in the composite oxide powder used as the air electrode material is reduced, the conductivity of the air electrode is improved. Furthermore, the inventors have decided to use the stated formula (1) as an indicator of the proportion of aggregated powder in the composite oxide powder.

[0037] “D 10 “D” 50 “D” 90 "These are the cumulative 10%, 50%, and 90% particle sizes on a volume basis, measured using a particle size distribution measuring device employing laser diffraction / scattering. In this specification, the MT3300EXII manufactured by Microtrac Bell is used as the particle size distribution measuring device." (D 90 -D 10 ) / D 50 "The smaller the size, the narrower the volumetric particle size distribution of the composite oxide powder; conversely, "(D 90 -D 10 ) / D 50 "The larger the value, the wider the volumetric particle size distribution of the composite oxide powder."

[0038] In this invention, 0.15 g of composite oxide powder was added to 60 mL of 500 ppm sodium hexametaphosphate aqueous solution (dissolved in deionized water). The volume particle size distribution of the composite oxide powder before and after ultrasonic dispersion was measured, and the particle size distribution (D6) before and after ultrasonic dispersion was calculated. 90 -D 10 ) / D 50 (Hereinafter, "B" will be added before ultrasonic dispersion and "A" will be added after ultrasonic dispersion to distinguish between the two.) The ratio of the calculated values ​​will be used as an indicator of the proportion of aggregated powder in the composite oxide powder. That is, since most of the aggregated powder is loosened and becomes primary particles through ultrasonic dispersion, the higher the content of aggregated powder in the composite oxide powder, the higher the "(D)" ratio after ultrasonic dispersion. 90A -D 10A ) / D 50A "Compared to the "(D) before ultrasonic dispersion" 90B -D 10B ) / D 50B "The smaller the value, the higher the content of aggregated powder in the composite oxide powder, {(D 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D 50A The larger the value of}, the better.

[0039] In this invention, the {(D 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D 50A Determine the range that satisfies the following equation (1).

[0040] 1≤{(D 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D 50A}≤2.1···(1)

[0041] When the above {(D) 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D 50A When the content of aggregated powder in the composite oxide powder is greater than 2.1, i.e., when the content of aggregated powder in the composite oxide powder is relatively high, it is not expected that the conductivity of the air electrode of the fuel cell made of composite oxide powder will be improved. The {(D 90B -D 10B ) / D50B} / {(D 90A -D 10A ) / D 50A The preferred upper limit value is 1.9. It should be noted that when the composite oxide powder does not contain aggregated powder, the ratio is "1".

[0042] The composite oxide powder involved in this embodiment, before ultrasonic dispersion, is measured using a Macquarie particle size distribution measuring device to determine the cumulative 50% particle size D based on volumetric particle size distribution. 50B Preferably, the particle size is 0.5 μm or larger and 3.0 μm or smaller. Furthermore, the cumulative 50% particle size D, calculated using a Macchick particle size distribution measuring device based on volumetric particle size distribution after ultrasonic dispersion, is... 50A Preferably, the micrometer size is 0.5μm or larger and 3.0μm or smaller.

[0043] (Manufacturing Method)

[0044] The method for manufacturing the composite oxide powder involved in this invention is not particularly limited, and an example of the manufacturing method will be described below. Methods for manufacturing composite oxide powder include a wet process in which a precursor is formed in a liquid and then heat-treated to form a composite oxide, and a dry process in which raw materials are weighed and then directly mixed and calcined to form a composite oxide. To achieve the objectives of this invention, manufacturing via a wet process is preferred. An example of a method for manufacturing composite oxide powder using a wet process will be given below, but appropriate adjustments can be made without departing from the spirit of the method described herein.

[0045] (Precursor preparation)

[0046] As a method for manufacturing the composite oxide powder according to this embodiment, the following method can be used: a raw material solution containing elements such as La dissolved in water or acid is added to an alkaline solution such as ammonia water in advance, and a neutralization reaction is carried out to generate a slurry containing the neutralization product of the composite oxide. The raw material is preferably a raw material that escapes in the form of gas during the calcination stage and does not remain as an impurity.

[0047] Preferably, the neutralization product contains carbonic acid. This prevents the localized formation of carbonates and crystallization during the separation and recovery of the neutralization product (sometimes referred to as the "precursor" in this specification). Consequently, the precipitation of impurity phases during perovskite mineralization in subsequent processes is suppressed, which is preferred. The carbonic acid can be added to the system in the form of a carbonate. The resulting neutralization product is amorphous nanoparticles with a uniform mixture of elements, thus facilitating element diffusion during calcination and promoting single-phase formation and microcrystal growth.

[0048] The temperature at which the neutralization product is formed is preferably below 60°C, more preferably below 50°C, and even more preferably below 40°C. By setting the temperature to such a level, substances in the liquid that easily turn into gas, such as carbonic acid and ammonia, will evaporate from the liquid, thus allowing for the appropriate formation of the neutralization product. In this embodiment, the neutralization product of the composite oxide is amorphous nanoparticles with uniformly mixed elements, thus achieving the effect of easy element diffusion during calcination and promoting single-phase formation and microcrystal growth.

[0049] (Filtering and drying)

[0050] The neutralized product is separated from the slurry as needed, washed, and dried to obtain a precursor obtained by drying the neutralized product. Methods for separating from the slurry include, for example, separation and recovery based on filtration, separation and recovery by pressure filtration, direct drying by spray drying, or freeze drying. For filtration and pressure filtration, known methods can be used. Furthermore, during direct drying, pH adjustment can be performed to adjust the obtained precursor to the desired size, etc. During pH adjustment, to avoid the presence of impurities such as alkali metals and alkaline earth metals in the dried aggregates, it is more preferable to use ammonia, which volatilizes during drying and leaves almost no residue, rather than using regulators containing alkali metals such as sodium hydroxide or potassium hydroxide. The drying temperature for drying the neutralized product is preferably 150°C or higher and 350°C or lower, more preferably 200°C or higher and 300°C or lower. Drying at temperatures far exceeding this range is not preferred because there is a possibility of some perovskite mineralization or incomplete drying resulting in residual moisture in the precursor.

[0051] (Precursor pulverizer)

[0052] The precursors for drying can be micronized by pulverization. Pulverization can be performed after the calcination process described later. Sometimes, pulverization is not necessary when using a spray dryer in the aforementioned drying process. Examples of pulverization devices, when using dry pulverization, include mortars, sample mills, Henschel mixers, hammer mills, spray mills, grinders, impeller mills, and impact mills. For example, when using an impact mill, the preferred rotational speed is between 9000 rpm and 16000 rpm. It should be noted that the rotational speed and pulverization time of the impact mill are related to the calcination temperature and time in the calcination process; the higher the calcination temperature or the longer the calcination time, the higher the rotational speed and the longer the pulverization time of the impact mill are preferred.

[0053] (Roasting)

[0054] The prepared precursor powder is calcined in a calcining furnace to obtain a composite oxide. The calcining furnace can be a conventionally known furnace with an electric or gas-fired heat source, such as a shuttle kiln, roller hearth kiln, or rotary kiln. Regarding the calcination temperature, to increase the crystallite diameter of the particles constituting the perovskite-type composite oxide powder, calcination at a temperature above 1000°C is preferred. Furthermore, when the calcination temperature is below 1500°C, the calcined product is prone to degranulation, which is also preferable.

[0055] The heating rate during calcination is set to below 10°C / min. The calcination atmosphere can be atmospheric or nitrogen containing more than 1 ppm and less than 20% oxygen. Slow calcination allows for adjustment of the crystallite diameter. Then, the calcination furnace or vessel is set as an open system, and the temperature is increased while removing gaseous components generated from the raw material salts. It should be noted that, in this invention, an open system refers to a reaction system in which the calcination furnace or vessel is not sealed and the atmosphere gas can flow in and out.

[0056] (Crushed)

[0057] Next, the calcined granules (calcined material) are pulverized. Pulverization can be performed by either wet pulverization or dry pulverization, or a combination of both. For dry pulverization, any of the apparatuses listed in the examples of the precursor pulverization can be used. Alternatively, when wet pulverization is used, wet ball mills, sand mills, grinding mills, bead mills, ultrasonic homogenizers, pressure homogenizers, and ultrafine pulverizers can be used. By using these for wet pulverization, perovskite-type composite oxides that meet the above conditions can be formed. In particular, bead mills are preferred. When selecting a bead mill for wet pulverization, any of the existing wet pulverizers such as vertical flow-through bead mills, horizontal flow-through bead mills, and high-intensity pulverizing rapid-flow viscous mills can be used, but horizontal flow-through bead mills are preferred. Compared to vertical flow-through bead mills, horizontal flow-through bead mills achieve more uniform pulverization during the residence period within the container, resulting in more uniform pulverization at the same flow rate, making them preferable. Furthermore, horizontal flow-through bead mills have a larger processing flow rate than high-intensity pulverizing rapid-flow viscous mills, making them economically advantageous. As the pulverizing medium, balls made from hard raw materials such as glass, ceramics, alumina, or zirconium oxide are preferred. To obtain perovskite-type composite oxides with the desired particle size, the ball particle size is preferably between approximately 0.1 mm and 5.0 mm, more preferably between 0.5 mm and 2.0 mm. As the dispersion medium used in wet pulverization, water or easily removable organic solvents with low boiling points, such as ethanol, can be used. From a production cost perspective, water is preferred as the dispersion medium.

[0058] In the case of wet pulverizing the calcined granules (calcined material), the pulverized material is dried to obtain a pulverized and dried product. Spray drying is preferred as the drying method. As the spray drying device, a spray dryer is preferred. Among them, a disc spray dryer is more preferred from the perspective of drying efficiency and mass production. The drying temperature is set to 60°C or higher and 350°C or lower, preferably 75°C or higher and 325°C or lower, and more preferably 100°C or higher and 300°C or lower. When drying is carried out at temperatures far exceeding this range, there is a possibility that some perovskite mineralization may occur, or sometimes the powder may not be completely dried and may contain residual moisture.

[0059] The pulverized material after dry grinding or the pulverized and dried material after wet grinding is subjected to a crushing process. It should be noted that "crushing" refers to loosening aggregated powder. As the crushing device, an apparatus designed for dry grinding can be used, where the rotational speed is set to a lower level than during grinding, i.e., a low rotation speed, to crush rather than grind the dried material. Preferably, the crushing device is a sample mill, Henschel mixer, hammer mill, jet mill, pulverizer, impeller mill, impact mill, or other apparatus capable of mechanical crushing. This crushing process further reduces the content of aggregates in the composite oxide powder. For example, when using a sample mill as the crushing device, it is preferable to set the rotational speed to a range of 1000 rpm to 4000 rpm.

[0060] (Sieving)

[0061] After drying the wet-milled material, coarse particles (agglomerated powder) are removed by sieving to obtain composite oxide powder. The sieve aperture used for sieving can be appropriately determined by considering factors such as the average primary particle size of the composite oxide powder (after ultrasonic dispersion). When the average primary particle size of the composite oxide powder is around tens of μm, the sieve aperture is preferably below 250 μm (above 60 mesh), and more preferably below 150 μm (above 100 mesh).

[0062] Regarding the particle size distribution of the calcined product (perovskite-type composite oxide powder) after sieving, the cumulative 50% particle size D was calculated using a volume-based particle size distribution measurement device before ultrasonic dispersion. 50B Preferably, the particle size is 0.5 μm or larger and 3.0 μm or smaller. Furthermore, the cumulative 50% particle size D, calculated using a Macchick particle size distribution measuring device based on volumetric particle size distribution after ultrasonic dispersion, is... 50A Preferably, the micrometer size is 0.5μm or larger and 3.0μm or smaller.

[0063] (Solid oxide fuel cell, SOFC)

[0064] Explanation of SOFC. Figure 1This is a schematic cross-sectional view of an example of an SOFC. It has a structure in which a thin plate or sheet-like fuel electrode 1 serving as a support, a solid electrolyte 2 formed on the surface of the fuel electrode 1, and a thin plate or sheet-like air electrode 3 formed on the surface of the solid electrolyte 2 are stacked.

[0065] Then, fuel gas (typically hydrogen (H2), but could also be hydrocarbons (methane (CH4)), etc.) is supplied to fuel electrode 1, and an oxygen-containing gas (air) flows to air electrode 3. When an electric current is applied to the fuel cell, the oxygen in the air is converted into oxide ions at air electrode 3. These oxide ions are then supplied from air electrode 3 to fuel electrode 1 via solid electrolyte 2. At fuel electrode 1, they react with the fuel gas to produce water (H2O), releasing electrons and generating electricity.

[0066] In the case of SOFC, although it also depends on the structure or manufacturing process of the fuel cell used, a stack of fuel electrode, solid electrolyte, etc. is prefabricated, a layer containing the air electrode material is formed on the stack by printing or vapor deposition, and then sintered to form an air electrode and manufacture a fuel cell.

[0067] The thickness of the air electrode film can be appropriately determined according to the battery structure, etc., and is not particularly limited. For example, it is preferably 20 μm or more and 50 μm or less. The material of the air electrode can be only the composite oxide powder of this embodiment, or it can be a mixture of perovskite composite oxide powders with different compositions or one or more perovskite composite oxide powders with different particle sizes with the composite oxide powder of this embodiment.

[0068] As a solid electrolyte, electrolyte materials used in the aforementioned air electrode materials can be used, such as rare earth element-doped cerium oxide solid oxide electrolytes and rare earth element-doped zirconium oxide solid oxide electrolytes.

[0069] The thickness of the solid electrolyte membrane is set to be thick enough to maintain the compactness of the solid electrolyte while being thin enough to provide the conductivity of oxygen or hydrogen ions, which are preferred for fuel cells, and to balance the two. It is preferably 0.1 μm or more and 50 μm or less, and more preferably 1 μm or more and 20 μm or less.

[0070] As a fuel electrode, it is acceptable to use materials previously used in SOFCs, as long as it has a porous structure and is configured to contact the supplied fuel gas. Examples include metal oxides composed of one or more metals and / or elements, including nickel (Ni), copper (Cu), gold (Au), platinum (Pt), palladium (Pd), ruthenium (Ru), other platinum group elements, cobalt (Co), lanthanum (La), strontium (Sr), and titanium (Ti). One or more of these elements may be used.

[0071] From the perspectives of durability and thermal expansion coefficient, the film thickness of the fuel electrode is preferably 20 μm or more and 1 mm or less, and more preferably 20 μm or more and 250 μm or less.

[0072] It should be noted that SOFCs can be fabricated in conventionally known planar, polygonal, tubular, or flat tubular shapes (where the circumferential sides of a cylinder are vertically flattened), and their shape or size is not particularly limited. Furthermore, as a planar SOFC, in addition to the anode-supported cell (ASC), electrolyte-supported cells (ESC) with a thick electrolyte layer or cathode-supported cells (CSC) with a thick air layer can be used. In addition, metal-supported cells (MSCs) with a porous metal sheet placed below the fuel electrode can also be fabricated.

[0073] Example

[0074] (Example 1)

[0075] (1) Pre-production

[0076] A solution prepared by dissolving lanthanum oxide in nitric acid (La concentration: 15.04% by mass, NO3-) - A mixed solution of nitrates, obtained by mixing 270g / L strontium nitrate (Sr(NO3)2) powder, 17.1g of manganese nitrate (Mn(NO3)2) aqueous solution with a concentration of 50.4% by mass, was prepared by dissolving 290g of strontium nitrate powder and 144.3g of manganese nitrate (Mn(NO3)2) aqueous solution with a concentration of 50.4% by mass, in 549.1g of ion-exchanged water.

[0077] In addition, 2670g of ion-exchanged water and 330g of ammonium carbonate were placed in a reaction vessel, and the water temperature was adjusted to 25°C while stirring. A mixed solution was slowly added to the ammonium carbonate solution, and a neutralization reaction was carried out at 25°C to precipitate the neutralization product of the perovskite-type composite oxide. The neutralization product was then aged for 30 minutes to end the reaction.

[0078] (2) Filtration and drying

[0079] The obtained neutralized product was filtered and washed with water, then shaped into slender cylindrical granules with a diameter of 5 mm. The granules were then immediately dried by heating at 250°C for 2 hours while being ventilated, yielding a black precursor.

[0080] (3) Roasting

[0081] 50g of the obtained precursor was placed in a round crucible (a container with a diameter of 90mm and a height of 75mm), and placed in an electric muffle furnace (Toyo Seisakusho KM-160). The temperature was increased from room temperature to 800℃ at a rate of 3.1℃ / min, and then increased from 800℃ to 1100℃ at a rate of 2.6℃ / min. The mixture was then calcined at 1100℃ (calcination temperature) for 2 hours, and then allowed to cool naturally to room temperature.

[0082] (4) Dry grinding

[0083] The obtained calcined material was pulverized using a sample milling device (manufactured by Kyoritsu Corporation, model name: SK-M10) at a feed rate of 20g / batch at a speed of 16000rpm for 30 seconds × 2 times to obtain composite oxide powder.

[0084] (5) Wet grinding

[0085] 50g of the obtained composite oxide powder, 200g of ZrO2 microspheres with a diameter of 1.0mm, and 93g of ion-exchanged water were placed in the jar of an Imex 4-cylinder sand mill (TSG-4U type, volume capacity: 350mL). The jar was then cooled with 20°C cooling water while being rotated at 1500rpm for 40 minutes for wet pulverization. The pulverized material containing the composite oxide was then dried as a slurry with solid components at 125°C. The slurry containing the composite oxide was then sprayed using a spray dryer (Okawahara Chemical Machinery Co., Ltd., model: FL-12) at an atomizer speed of 20000rpm and a slurry feed rate of 160g / min, while granulation drying was performed at a drying temperature of 200°C.

[0086] (6) Broken

[0087] The process involved multiple wet pulverization steps to obtain 200g of dried powder. The dried powder was then crushed using a sample mill (Dalton, model KIIWR-1, sieve with a dot diameter of 1mm) at 3600rpm.

[0088] (7) Screening

[0089] The dried powder was sieved using a vibrating screen (Verder Scientific, model: AS200) with a sieve of 500 μm (30 mesh) to obtain the composite oxide powder involved in Example 1.

[0090] The physical properties of the obtained composite oxide powder were determined using the following methods. The results are shown in Table 1.

[0091] In addition, the obtained composite oxide powder was analyzed by X-ray diffraction, which will be described later, and the results confirmed that it was a single-phase perovskite type composite oxide powder.

[0092] (Comparative Example 1)

[0093] Except for the absence of a crushing process following wet pulverization, the composite oxide powder involved in Comparative Example 1 was obtained in the same manner as in Example 1.

[0094] The physical properties of the obtained composite oxide powder were determined using the following methods. The results are shown in Table 1.

[0095] In addition, X-ray diffraction analysis, similar to the example, confirmed that it was a single-phase perovskite-type composite oxide powder.

[0096] (Composition Analysis)

[0097] The composition of the composite oxide powder was analyzed using an inductively coupled plasma (ICP) luminescence analyzer (Agilent Technologies 720ES).

[0098] (BET specific surface area)

[0099] The BET specific surface area of ​​the obtained composite oxide powder was determined using the BET single-point method with a BET specific surface area measuring device (Yuasa Ionics 4Sorb US).

[0100] (Before particle size distribution determination and ultrasonic dispersion treatment)

[0101] A slurry containing composite oxide powder was prepared by adding 0.15 g of the obtained composite oxide powder to 60 mL of a 500 ppm sodium hexametaphosphate aqueous solution (dissolved in deionized water). The cumulative 10% particle size (D) of the composite oxide powder was determined using a Macchique particle size distribution analyzer (NTXS MT3300EXII) (particle refractive index set to 2.40, solvent refractive index set to 1.333, calculation mode set to MT3300II). 10B ), cumulative 50% particle size (D 50B ), cumulative 90% particle size (D 90B ).

[0102] (After particle size distribution determination and ultrasonic dispersion treatment)

[0103] A slurry containing composite oxide powder was obtained by adding 0.15 g of the obtained composite oxide powder to 60 mL of 500 ppm sodium hexametaphosphate aqueous solution (dissolved in deionized water) and dispersing it for 30 seconds using an ultrasonic homogenizer (US-600TCVP, Nippon Seiki Co., Ltd.) at an ultrasonic power of 300 μA. The cumulative 10% particle size (D) of the composite oxide powder was measured using a Mack particle size distribution measuring device (MT3300EXII, Nikkiso Co., Ltd.) (with particle refractive index set to 2.40, solvent refractive index set to 1.333, and calculation mode set to MT3300II). 10A ), cumulative 50% particle size (D 50A ), cumulative 90% particle size (D 90A ).

[0104] (Conductivity Measurement)

[0105] Two g of composite oxide powder was placed into a cell with a radius of 10 mm. The powder was pressed using a powder resistivity measuring system (MCP-PD51, Mitsubishi Chemical Analytech) at a pressure of 8 kN. The conductivity was then measured using a resistivity meter (MCP-T610, Mitsubishi Chemical Analytech) via a four-probe method. The absolute values ​​measured are shown in Table 1, with a ratio to Comparative Example 1.

[0106] (X-ray diffraction measurement)

[0107] The obtained composite oxide powder was subjected to XRD analysis using Rigaku's Ultima IV. The measurement conditions were as follows: Cu lamp, tube voltage of 40 kV, tube current of 40 mA, divergence slit of 1 / 2°, scattering slit of 8 mm, receiving slit set to open, step size of 0.02°, and measurement time set to 4° / minute. Based on the obtained X-ray diffraction pattern, the crystal phase of the obtained composite oxide powder was identified using the analysis software accompanying the XRD apparatus (Rigaku's Integrated Powder X-ray Analysis Software PDXL2 with ICDS (Inorganic Crystal Structure Database)).

[0108] [Table 1]

[0109]

[0110] Analysis of the composition of the composite oxide powder using an ICP-based luminescence analyzer revealed that the composite oxide powders of Example 1 and Comparative Example 1 have the following compositional formula: La. 0.8 Sr 0.2 Mn1.0 O3 was confirmed to be a single-phase perovskite-type composite oxide powder by X-ray diffraction.

[0111] The specific surface area of ​​BET is 4.23 m². 2 / g、{(D 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D 50A The composite oxide powder of Example 1, which has a conductivity of 1.14 and contains almost no aggregates, has a conductivity of 2378 μS / cm, while {(D 90B -D 10B ) / D 50B} / {(D 90A -D 10A ) / D 50A The composite oxide powder of Comparative Example 1, which has a conductivity of 3.95 and contains more aggregates, has a conductivity of 1980 μS / cm, which is lower than that of the composite oxide powder of Example 1.

[0112] Industrial availability

[0113] According to the present invention, perovskite-type composite oxide powders with higher conductivity can be realized. By using such perovskite-type composite oxide powders, air electrodes and fuel cells with high conductivity can be realized.

[0114] Explanation of reference numerals in the attached figures

[0115] 1 fuel electrode

[0116] 2 Solid electrolytes

[0117] 3 air poles

Claims

1. A perovskite-type composite oxide powder, characterized in that: It contains La and further contains at least one element selected from the group consisting of Sr, Ca, Co, Ni, Mn, and Fe, The BET specific surface area of ​​the perovskite-type composite oxide powder is less than 6.0 m 2 / g, And satisfy the following formula (1), 1≤{(D 90B -D 10B ) / D 50B } / {(D 90A -D 10A ) / D 50A }≤2.1··· (1) In the formula, D 10A , D 50A , D 90A The cumulative 10% particle size (D 10A ), cumulative 50% particle size (D 50A ), cumulative 90% particle size (D 90A ), the slurry containing the perovskite-type composite oxide powder is obtained by adding 0.15 g of the perovskite-type composite oxide powder to 60 mL of a 500 ppm aqueous sodium hexametaphosphate solution (dissolved in ion-exchanged water) and dispersing the mixture for 30 seconds using an ultrasonic homogenizer at an ultrasonic power of 300 μA; D 10B , D 50B , D 90B The cumulative 10% particle size (D) based on volume when measuring a slurry containing a perovskite-type composite oxide powder using a Microtrac particle size distribution analyzer. 10B ), cumulative 50% particle size (D 50B ), cumulative 90% particle size (D 90B ), the slurry containing the perovskite-type composite oxide powder is obtained by adding 0.15 g of the perovskite-type composite oxide powder to 60 mL of a 500 ppm aqueous sodium hexametaphosphate solution (dissolved in ion-exchanged water).

2. The perovskite-type composite oxide powder according to claim 1, wherein Cumulative 50% particle size based on volume (D 50B ) is in the range of 0.5 μm or more and 1.3 μm or less.

3. An air electrode for a solid oxide fuel cell, comprising the perovskite type composite oxide powder according to claim 1 or 2.

4. A solid oxide fuel cell comprising a fuel electrode, a solid electrolyte and an air electrode, wherein: The air electrode according to claim 3 is used as the air electrode.

Citation Information

Patent Citations

  • Air electrode material powder of solid oxide fuel cell, air electrode and solid oxide fuel cell

    JP2006032132A

  • Gas sensor element and gas sensor

    JP2018112490A

  • Perovskite-type composite oxide powder

    WO2022013903A1

  • Method for producing perovskite compound powder

    CN101014538A

  • Powder for solid oxide fuel cell air electrode, and method for manufacturing said powder for solid oxide fuel cell air electrode

    CN113574705A